Untersuchungen zur Sensibilität von Seefischen an Bord - Münkner, Werner; Kuhlmann, Holmer; Oehlenschläger, Jörg (1998)
First orientating investigations of the sensitiveness of the fish species dab (Limanda limanda), plaice (Pleuronectes platessa) and cod (Gadus morhua) immediately after catch and after different duration of bulk storage were carried out on board the fishing research vessel “Solea”. The aim of the investigations was to get an idea wether or not the central nervous system of the fishes was in function and the fishes could suffer pain. The proportion of sensitive dab, plaice and cod immediately after the catch was higher than 70, 80 and 95 %, respectively. After 30 min of bulk storage the percentage was reduced to 50, 60 and 70 % resp., after 90 minutes to 5, 15 % and 35 %. In cod it decreased further to 5 % after 120 min. An influence of trawling time (0,5 - 2 h) or size of the catch (100 to 1000 kg) on the number of sensitive animals was not found. Although fishing parameters in commercial fishery will in most cases put a stronger mechanical stress on the animals during trawling and handling on board a certain number of sensitive fish can still be expected.